DIPG-23. EFFICACY OF THE SOLUBLE PANOBINOSTAT (MTX110) IN PRECLINICAL DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG) MODELS. (23rd April 2019) - Truffaux, Nathalene; Yang, Xiaodong; Hadaczek, Piotr; Bankiewicz, Krystof; Damment, Stephen J P; Mueller, Sabine
Abstract: INTRODUCTION: Large drug screening and preclinical studies identified the pan-histone deacetylate inhibitor panobinostat as a promising treatment for DIPG. However, blood brain barrier functional integrity in DIPG limits drug penetration and remains a key cause of resistance to therapies. Therefore, we explored the therapeutic potential of water-soluble formulation of panobinostat MTX110 in our preclinical models and tested the efficacy in DIPG in vivo models using convection-enhanced delivery (CED). METHODS: CellTiter-Glo assay was used assess antiproliferative effects in DIPG derived cell lines (SF8628, NEM157, SF10423, SF10693). Effect on cell cycle was assessed using FACS analysis. To test safety, concentrations from 30 uM to 3000 uM were administered via CED into the striatum of the rat brain. In vivo activity of MTX110 via CED was assessed using a DIPG patient derived model (SF8628). RESULTS: MTX100 showed a strong antiproliferative and cytostatic effect on halting progression through G0/G1 in all tested DIPG cell lines with similar efficacy than the original formulation at submicromolar concentrations. Immunohistochemistry analysis showed no significant changes in doses up to 1000uM. CED of 100uM MTX110 significantly prolonged survival (control: median survival 52 days; MTX CED: median survival 64 days; p=0.0372). CONCLUSION: Our study confirmed that CED administration of MTX110 provides a potent antitumor effect. An ongoing trial is testing the safety and efficacy of CED of MTX110 in newly diagnosed patients.